2020
DOI: 10.1007/s11606-020-06056-x
|View full text |Cite
|
Sign up to set email alerts
|

Lifestyle Habits Associated with Weight Regain After Intentional Loss in Primary Care Patients Participating in a Randomized Trial

Abstract: BACKGROUND: Though long-term weight loss maintenance is the treatment goal for obesity, weight regain is typical and few studies have evaluated lifestyle habits associated with weight regain. OBJECTIVE: To identify dietary and physical activity habits associated with 6-and 24-month weight regain among participants in a weight loss maintenance clinical trial. DESIGN: Secondary analysis of randomized clinical trial data. PARTICIPANTS: Adult primary care patients with recent, intentional weight loss of at least 5… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…As is typically the case with RCT-based cost-utility analyses, longterm health effects beyond the duration of the MERIT study were extrapolated, introducing uncertainty into our analysis. Whilst durable total body weight loss over the longer term with ESG has been shown in a previous 5-year prospective cohort study by Sharaiha et al [53], recidivism following modest initial weight loss is often observed with LM alone [53][54][55][56]. Inclusion of a weight regain assumption for 20% of patients receiving ESG in the base case represents a strength of our analysis.…”
Section: Limitationsmentioning
confidence: 82%
“…As is typically the case with RCT-based cost-utility analyses, longterm health effects beyond the duration of the MERIT study were extrapolated, introducing uncertainty into our analysis. Whilst durable total body weight loss over the longer term with ESG has been shown in a previous 5-year prospective cohort study by Sharaiha et al [53], recidivism following modest initial weight loss is often observed with LM alone [53][54][55][56]. Inclusion of a weight regain assumption for 20% of patients receiving ESG in the base case represents a strength of our analysis.…”
Section: Limitationsmentioning
confidence: 82%
“…To date, the work in this area has been largely observational and examined specific dietary intake behaviors, self-monitoring (e.g., frequent self-weighing) patterns, and PA habits that are associated with weight regain (6,15), although we recently reported detailed dietary behavior strategies associated with weight regain in the MAINTAIN-pc trial (16). Findings are relatively consistent and show that decreased intake of dietary fat and sugar-sweetened beverages, increased fruit and vegetable intake, utilization of portion control/meal replacements, decreased eating out, frequent self-weighing, and high PA levels are associated with less weight regain over time (6,(15)(16)(17). However, this prior work has not evaluated other lifestyle strategies for maintaining weight loss, such as professional support.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, participants in the coaching group received personalized coaching via their patient portal account in the EHR. Participants were contacted regularly (weekly for month 1, biweekly for months 2-5, monthly for months 6-12, and quarterly for months [13][14][15][16][17][18][19][20][21][22][23][24] by trained health coaches. The trained health coaches in this trial had backgrounds in nursing, nutrition, and exercise physiology.…”
Section: Study Overviewmentioning
confidence: 99%
“…Increased exercise is required because there is a decrease in basal metabolism with weight loss, so increasing exercise allows for a higher calorie intake per day, which may be more sustainable. Additionally, eating more restaurant meals has been associated with weight regain [ 71 ], so encouraging patients to prepare most of their meals at home may help.…”
Section: A Review On Current Treatments For Obesitymentioning
confidence: 99%